Pinning effect of reactive elements on adhesion energy and adhesive strength of incoherent Al2O3/NiAl interface. Issue 33 (2nd August 2016) - Zhang, Z.; Zhang, R. F.; Legut, D.; Li, D. Q.; Zhang, S. H.; Fu, Z. H.; Guo, H. B.
Abstract : We perform density functional theory calculations and information targeted experiments to reveal the origin of the enhancement of interface adhesion in thermal barrier coatings by doping with reactive elements. Abstract : The profound effects of reactive elements (REs) on the adhesion energy and adhesive strength of the α-Al2 O3 /β-NiAl interface in thermal barrier coating (TBC) systems have attracted increasing attention because RE-doping has played a significant role in improving the thermal cycling lifetime of TBCs. However, the fundamental mechanism is, so far, not well understood due to the experimental difficulty and theoretical complexity in interface modelling. For this purpose, in the present study we have performed comprehensive density functional theory calculations and information targeted experiments to underline the origin of the surprising enhancement of interface adhesion, stability and mechanical strength of the α-Al2 O3 /β-NiAl interface by different RE doping levels. Our results suggest that the interface failure firstly appears within the NiAl layer adjacent to the Al-terminated oxide under mechanical loading, while the formation of O–RE–Ni bond pairs at the interface can effectively hinder the interface de-cohesion, providing a higher mechanical strength. By comparing several typical REs, it is observed that Hf can emerge not only with the highest interface adhesion energy, but also the highest mechanical strength; in agreement with our experimental results. By continuously increasing the dopant concentration, the strengthening effect may increase correspondingly, but is limited by the solute solubility. These results shed light into the effect of REs on the stability and strength of the α-Al2 O3 /β-NiAl interface, providing theoretical guidance for interface design via a combinational analysis of bond topology and electronic structure.